2015
DOI: 10.1039/c5an00635j
|View full text |Cite
|
Sign up to set email alerts
|

DNA-functionalized upconversion nanoparticles as biosensors for rapid, sensitive, and selective detection of Hg2+ in complex matrices

Abstract: We have developed a facile one-step approach to make hydrophilic and DNA-functionalizable upconversion nanoparticles (UCNPs), which are used to act as a biosensor for determining Hg(2+) in complex matrices. The proposed approach is simple and exhibits low background interference, high sensitivity and rapid response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…As previously mentioned, UCNPs with large anti‐Stokes shift, weak background interference, and no photobleaching are suitable to detect some target species, such as pH, temperature, metal ions, anion, free radicals, biological molecules, and so on . Most cases of detection are based on LRET process with a few exceptional cases.…”
Section: Applications Of Upconversion Nanostructuresmentioning
confidence: 99%
“…As previously mentioned, UCNPs with large anti‐Stokes shift, weak background interference, and no photobleaching are suitable to detect some target species, such as pH, temperature, metal ions, anion, free radicals, biological molecules, and so on . Most cases of detection are based on LRET process with a few exceptional cases.…”
Section: Applications Of Upconversion Nanostructuresmentioning
confidence: 99%
“…Several nanoparticles have been used to construct fluorescence sensors including carbon dots (CDs), 116 , 149 quantum dots (QDs), 126 , 150 152 or up-conversion NPs. 153 Using multicolor QDs, Zhang et al ( 151 ) showed the feasibility of detecting SARS-CoV-2 using a portable system. A smartphone-based portable device is used to read a barcode-like signal to track the SARS-CoV-2 infection.…”
Section: Diagnostic Tests Of Sars-cov-2 Based On Nanomaterials and 2d...mentioning
confidence: 99%
“…[68] Besides these studies, there are also some other strategies reported in literature. For example, Chu and co-workers reported a DNA-functionalized UCNPs probe to sense Hg 2+ with a detection limit of 5 × 10 −9 m [69] while some other groups employed rhodamine-derivative-functionalized upconversion nanorods to recognize Hg 2+ . [70][71][72]…”
Section: Hg 2+ Sensorsmentioning
confidence: 99%